Activation of GSDMD contributes to acute kidney injury induced by cisplatin - Li, Yuanyuan; Xia, Weiwei; Wu, Mengying; Yin, Jie; Wang, Qian; Li, Shuzhen; Zhang, Aihua; Huang, Songming; Zhang, Yue; Jia, Zhanjun (American journal of physiology. Renal physiology, 2020)
Cisplatin is one of the most effective antitumor agents, but its clinical use is highly limited by its severe side effects, especially nephrotoxicity. Recently, the active form of gasdermin D (GSDMD), termed GSDMD-N, was identified to mediate pyroptotic inflammatory cell death in several diseases. However, the role of the GSDMD-N fragment in cisplatin-induced acute kidney injury (AKI) remains unclear. In the present study, we found that pyroptosis was induced by cisplatin in both mouse kidney tissues and renal tubular epithelial cells, accompanied by increased expression of the GSDMD-N fragment. In GSDMD knockout mice with cisplatin-induced AKI, we found that cisplatin-induced loss of renal function, renal tubular injury, and inflammation was significantly attenuated compared with wild-type mice. Furthermore, the GSDMD-N fragment was overexpressed by an established rapid plasmid tail vein injection approach to evaluate the role of this cleaved form of GSDMD in AKI. As expected, mice with GSDMD-N fragment overexpression in the kidney were more susceptible to cisplatin-induced AKI than control mice, as evidenced by further elevated serum levels of blood urea nitrogen and creatinine, aggravated renal pathology, increased expression of neutrophil gelatinase-associated lipocalin and kidney injury molecule-1, and enhanced renal inflammatory cytokine secretion, which indicates a pathogenic role of GSDMD-N in cisplatin-induced AKI by triggering cell pyroptosis. Similar results were also observed in renal tubular epithelial cells overexpressing the GSDMD-N fragment. Thus these findings suggested that the activation of GSDMD contributes to cisplatin-induced AKI, possibly through triggering pyroptosis.